Representation of Luxury in Female Indonesian Instagram Influencers: A Barthesian Semiotic Analysis - Rusyda Nazhirah Yunus; Berliansyah Rumodhon; Luki Aswar (International Journal of Multilingual Education and Applied Linguistics, 2025)
Instagram has become one of the most influential digital platforms for the construction and dissemination of lifestyle meanings, particularly through the presence of social media influencers. Among various lifestyle narratives, luxury is one of the most dominant and ideologically loaded representations circulated by influencers. This study examines how luxury is represented, constructed, and naturalized in the Instagram content of female Indonesian influencers using Roland Barthes’ semiotic framework. The object of this research consists of visual and textual Instagram posts that display luxury-related lifestyles, including fashion, travel, leisure, and consumption practices. The main problem addressed in this study concerns how signs of luxury operate at the levels of denotation, connotation, and myth to shape audience perceptions of success, femininity, and social status. The objective of this research is to reveal the ideological meanings embedded in influencer content and to explain how luxury is transformed into a normalized and desirable lifestyle. This study employs a qualitative descriptive method with semiotic analysis. Data were collected through purposive sampling of Instagram posts from selected female Indonesian influencers with significant follower engagement. The findings show that luxury is represented not merely through high-priced commodities but through symbolic systems involving aesthetics, body presentation, spatial settings, and narrative captions. At the mythological level, luxury is naturalized as the result of personal effort, self-discipline, and modern femininity, thereby obscuring structural inequalities and reinforcing consumerist ideology. This study concludes that Instagram influencers function as cultural agents who reproduce dominant myths of success and luxury in digital culture.